2017
DOI: 10.5588/ijtld.16.0418
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism: epidemiological data and diagnosis in Kinshasa hospitals

Abstract: PE is common in Kinshasa, with characteristics similar to those reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 0 publications
4
13
0
Order By: Relevance
“…Moreover, 1-month mortality was found to be similar in both groups (8.3% in the patients younger group and 6.2% in the patients elder group). The findings about the mortality rate can be said to be in conformity with the findings of other studies (11).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, 1-month mortality was found to be similar in both groups (8.3% in the patients younger group and 6.2% in the patients elder group). The findings about the mortality rate can be said to be in conformity with the findings of other studies (11).…”
Section: Discussionsupporting
confidence: 90%
“…The second most frequently observed risk factor was chronic cardiac and/or pulmonary diseases with a ratio of 15.4%, followed by cancer with a ratio of 14.7%. A recent study by Bakabe A. et al reported immobilization as the most common risk factor with a ratio of 43% (11,12). Husain SJ.…”
Section: Discussionmentioning
confidence: 98%
“…Most studies report data on PE prevalence for in-hospital population. The prevalence of PE has been reported as high as 37% among selected hospitalized patients [12] while others reported a prevalence of 0.6% for subjects reporting syncope in the emergency department [13] and 16.1% in patients suffering from acute exacerbation of pulmonary embolism [14]. We have estimated PE prevalence by assessing the number of prescriptions by Social Security Number so that we would not have patient replicates counted more than one time so our study gives a rather fair estimate of the disease prevalence on the general population of Greece.…”
Section: Discussionmentioning
confidence: 99%
“…• Pulmonary embolism: Thrombus in the pulmonary artery was confirmed by computed Tomography pulmonary angiography [12].…”
Section: Conceptual Definition Of Termsmentioning
confidence: 99%